2016
DOI: 10.1016/j.jacc.2016.03.508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D on Cardiac Function in Patients With Chronic HF

Abstract: BackgroundPatients with chronic heart failure (HF) secondary to left ventricular systolic dysfunction (LVSD) are frequently deficient in vitamin D. Low vitamin D levels are associated with a worse prognosis.ObjectivesThe VINDICATE (VitamIN D treatIng patients with Chronic heArT failurE) study was undertaken to establish safety and efficacy of high-dose 25 (OH) vitamin D3 (cholecalciferol) supplementation in patients with chronic HF due to LVSD.MethodsWe enrolled 229 patients (179 men) with chronic HF due to LV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
129
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 201 publications
(137 citation statements)
references
References 42 publications
2
129
1
5
Order By: Relevance
“…Moreover, the median age of participants was 54yrs, with an unusually high (80%) device therapy rate, the study included people who were sufficient in 25[OH] D (concentrations 50-75 mmol/L) and the group assigned vitamin D supplementation had significantly worse renal function and was 2 years older. In contrast, participants in our two studies and the present cohort study were ambulant outpatients, mean age 70 years with a more typical device therapy rate (30%) and all had 25[OH]D concentrations < 50 nmol/L [12].…”
Section: Vitamin D As An Interventionmentioning
confidence: 66%
See 1 more Smart Citation
“…Moreover, the median age of participants was 54yrs, with an unusually high (80%) device therapy rate, the study included people who were sufficient in 25[OH] D (concentrations 50-75 mmol/L) and the group assigned vitamin D supplementation had significantly worse renal function and was 2 years older. In contrast, participants in our two studies and the present cohort study were ambulant outpatients, mean age 70 years with a more typical device therapy rate (30%) and all had 25[OH]D concentrations < 50 nmol/L [12].…”
Section: Vitamin D As An Interventionmentioning
confidence: 66%
“…Vitamin D has multiple effects throughout the body that may be of particular relevance in people with CHF [11]. We have recently described in a randomised, placebo-controlled trial in unselected ambulatory patients with CHF and 25 [OH]D deficiency that vitamin D 3 supplementation (100 mcg (4000 IU) daily) improves left ventricular structure and function [12]. Whether 25[OH]D deficiency independently predicts outcomes in unselected patients with CHF remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Fok1) gene [8589]. Improvement and beneficial effects of vitamin D on LV structure and function in the VINDICATE (VitamIN D treatIng patients with Chronic heArT failurE) study in HF [90] and decreased renin activity with short-term vitamin D supplementation in chronic HF patients [91] suggest the therapeutic role of vitamin D (Table 1). …”
Section: Cardiac Diseasesmentioning
confidence: 99%
“…Yet, it has been recently demonstrated that high-dose vitamin D supplementation for 1-year in patients with chronic heart failure due to left ventricular systolic dysfunction and vitamin D deficiency, on contemporary optimal medical therapy, resulted in a significant improvement in left ventricular structure and function[59]. Of note, in almost 60% of these patients, the etiology was ischemic heart disease, suggesting a possible beneficial effect on post-AMI ventricular dysfunction[59]. …”
Section: Introductionmentioning
confidence: 99%